Hubungan Aktivitas Screen Time Terhadap Perkembangan Emosional Anak Usia 4-5 Tahun - Putri, Ananda Ghia; Stellata, Alyxia Gita; Rahmi, Sania Lailatu (Jurnal Bidan Mandiri, 2025)
The Health Office of Bukittinggi City reported that out of 11,383 toddlers, 2,742 (24.48%) experienced emotional development disorders. Emotional development in children is influenced by their environment and play habits, including screen time activity. This study aims to determine the relationship between screen time activity and the emotional development of children aged 4–5 years in the Guguk Panjang District, Bukittinggi City, in 2025. This research is an analytical survey with a cross-sectional design conducted from May 20 to June 4, 2025, at PAUD/TK Aisyiyah I Guguk Panjang. The study population consisted of children aged 4–5 years, with a total sample of 35 respondents selected using accidental sampling. Data were collected through questionnaires on screen time activity and children's emotional development. The data were analyzed using univariate and bivariate methods with a chi-square test and a significance level of 0.05. The results showed that most of the children aged 4–5 years had poor screen time activity, with 17 respondents (48.6%). Furthermore, most children had poor emotional development, with 30 respondents (85.7%). Statistical tests showed a significant relationship between screen time activity and emotional development in children aged 4–5 years (p-value = 0.016). These findings indicate that most of the problems in children's emotional development are caused by screen time activities. The conclusion of this study is that there is a relationship between screen time activity and the emotional development of children aged 4–5 years. Therefore, it is recommended that screen time activities for children in this age group should not be introduced early or should be controlled and accompanied. Parents are encouraged to divert their children's attention from gadgets by introducing educational games that can stimulate child development.